Peran Metode Discovery Learning dalam pembelajaran IPA Terpadu - Sri Muliani; Sugitmi Sugitmi; Muhammad Komarul Huda (Mahesa Research Center, 2022)
The teacher's learning process activities are expected to be able to guide and help students to be more creative and more active, it is due to increase student interest in learning. To determine success in the learning process to be implemented, several learning methods such as the discovery method are needed. Discovery learning learning method is a teaching procedure that emphasizes individual teaching, object manipulation, etc., which links science, environment, technology and interacting society. The existence of the discovery learning method in learning can improve students' creativity and skills. The development of this discovery method can help students to be able to adapt to reality not fantasy, make students think broadly and creatively, can solve any problems that arise, and students become wise in make decision.